Investigating Steroid-associated Peptic Symptoms in Patients With Primary Nephrotic Syndrome: Steroid-associated Peptic Symptoms in Nephrotic Syndrome - Khansari, Shabnam; Bazargani, Behnaz; Abbasi, Arash; Fahimi, Daryoosh; Askarian, Fahimeh; Moghtaderi, Mastaneh (Journal of Pediatric Nephrology, 2024)
Background and Aim: Nephrotic syndrome is the most common glomerulopathy among children aged 2-10 years old and high doses of corticosteroids are the cornerstone of its management. Whether corticosteroid use induces peptic ulcer disease in these patients remains uncertain. This study explores any relation between steroids and peptic symptoms in these children. Methods: A total of 100 nephrotic syndrome patients aged 1 to 15 years old treated with oral prednisolone in our Outpatient Department were studied. In this study, we compared nephrotic syndrome patients receiving 2 mg/kg prednisolone daily for 1 month and afterward as every other day until tapering off in about 3-6 months. They were divided into groups. One received aluminum Mg (Al-Mg) or proton pump inhibitors (PPIs) as prophylaxis and the other 50 patients did not receive any prophylaxis. These two groups are investigated for any gastro-intestinal complications. Heartburn, hematochezia, nausea, and dyspepsia are the four complications that were studied. Results: In this study, the data from 100 patients (61 male and 39 female) were analyzed. Accordingly, 46% of the patients consumed 0.5 mg/kg prednisolone every other day and 19% of the patients consumed 2 mg/kg prednisolone daily. In 51% of patients the duration of treatment was more than 6 months and in 19% of cases it was less than a month. Also, among the 68% of the patients who did not take PPIs, none experienced any digestive symptoms, including hematochezia. Among those patients who received prophylactic, PPIs one patient with less than a month of prednisolone taking and one who took prednisolone for more than six months contracted hematochezia. Conclusion: One-month therapy regimen of 2 mg/kg daily prednisolone and continuation of it until tapering off the steroids causes few gastrointestinal symptoms. The use of PPIs or Al-Mg did not affect the incidence of gastrointestinal symptoms significantly. Accordingly, corticosteroid therapy does not increase peptic ulcers in nephrotic syndrome patients.